BSEd Mathematics Students’ Geometry Problem-Solving Skills and Van Hiele Levels of Thinking - John Leo M. Mobe; Jean Rose V. Napilay; Mizzy B. Taytayon; Rhys Jr C. Cañon; Abdul J. Jamara (Applied AI and Machine Learning Journal, 2026)
Purpose: This study assessed the problem-solving skills of Bachelor of Secondary Education (BSEd) major in Mathematics students in Geometry using Van Hiele’s level-of-thinking theory. Research Methodology: This study employed a quantitative, non-experimental descriptive design to examine differences in students’ problem-solving skills in geometry based on their profiles. Participants were randomly selected, and data were collected using the Van Hiele Geometry Test (VHGT) and the Geometry Problem Solving Questionnaire (GPSQ). Statistical analyses included frequency, mean, standard deviation, and Welch’s analysis of variance (ANOVA). Results: Nearly half of the participants (45%) were categorized as Not Fit, indicating insufficient background knowledge in geometric thinking for the Van Hiele hierarchy. Statistical analysis showed p-values of 0.326 and 0.255, providing insufficient evidence to reject the null hypothesis. These findings suggest that the problem-solving skills of BSEd Mathematics students do not significantly differ across age groups or year levels. Conclusions: The analysis established that no significant difference exists in students’ problem-solving skills when grouped based on the demographic profile, which are age, gender, and year level, whose p-values are 0.326, 0.255, and 0.575, respectively. Limitations: This study needs to be investigated further by conducting studies that investigate other elements that influence students’ problem-solving abilities in geometry. In addition, the study was limited to a single institution (Davao del Norte State College), which lacks generalizability of results. Contributions: These findings suggest that mathematics teachers are recommended to utilize diverse and interactive instructional strategies that will improve and develop students’ geometric problem-solving skills that is outlined in Van Hiele levels of thinking.